2018
DOI: 10.3390/v10030112
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MAP2 and NF-H Associated with Dendritic Pathology in the Spinal Cord of Mice Infected with Rabies Virus

Abstract: Rabies is a viral infection that targets the nervous system, specifically neurons. The clinical manifestations of the disease are dramatic and their outcome fatal; paradoxically, conventional histopathological descriptions reveal only subtle changes in the affected nervous tissue. Some researchers have considered that the pathophysiology of rabies is based more on biochemical changes than on structural alterations, as is the case with some psychiatric diseases. However, we believe that it has been necessary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In spite of the severe neurological signs, pathological lesions typical of other viral encephalitis such as gliosis, perivascular lymphocytic infiltration, phagocytosis of neurons or neuronal apoptosis are rarely observed in rabies patients during the acute disease [18][19][20]. However structural damage to neurites such as focal axonal swelling, segmental demyelination and impairment of synaptic transmission are observed in natural [21][22][23][24][25] and experimental rabies infections [26][27][28][29][30][31]. This evidence suggests that rabies infection could induce pathological damage to the axons and dendrites of neurons without affecting the neuronal cell body.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the severe neurological signs, pathological lesions typical of other viral encephalitis such as gliosis, perivascular lymphocytic infiltration, phagocytosis of neurons or neuronal apoptosis are rarely observed in rabies patients during the acute disease [18][19][20]. However structural damage to neurites such as focal axonal swelling, segmental demyelination and impairment of synaptic transmission are observed in natural [21][22][23][24][25] and experimental rabies infections [26][27][28][29][30][31]. This evidence suggests that rabies infection could induce pathological damage to the axons and dendrites of neurons without affecting the neuronal cell body.…”
Section: Introductionmentioning
confidence: 99%
“…First, the current staining frequently results in incomplete vasculature. The residual blood within the tissue will affect the staining, and the neuronal structure will be interfered with the incomplete vascular structure (Mizutani et al 2008(Mizutani et al , 2010Gaballa and Goldman 1999;Monroy-Gomez et al 2018). However, few studies have mentioned how to improve this issue (Rosoklija et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While viruses are obligate intracellular parasites that have a life cycle requiring the engagements and modification of cytoskeleton at all stages, from invasion through replication to budding and transmission. By far, lots of viruses have been reported that evolved to engage and subvert the cytoskeleton proteins' function, such as RSV (Shahriari et al, 2016 ), Dengue Virus (Wang et al, 2010 ), Rubella virus (Krater et al, 2018 ), avian influenza viruses (Guo et al, 2018 ), rabies virus (Monroy-Gomez et al, 2018 ), Rhinovirus (Michi and Proud, 2018 ). In the present study, the microtubule-associated proteins Tubb5, Tuba3, the intermediate filament proteins Prph, Vim, and microfilament-associated protein Capza1 were down-regulated by echovirus infection, while microfilament-associated protein Actb and keratin-associated protein Krt83 were up-regulated.…”
Section: Discussionmentioning
confidence: 99%